2008
DOI: 10.1016/j.tecto.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and preservation of the Miocene Atacama Gravels in the Pedernales–Chañaral Area, Northern Chile: Climatic or tectonic control?

Abstract: In recent years, longitudinal changes on the thin/thick-skinned tectonic styles of the Central Andes has been intensively discussed while other studies have considered the role of mass transfers on the unloading the orogen, and on the stress regime along the plate interface arising from changes on the volume of sediment arriving into the Peru-Chile trench. The search for paleo-climate records is therefore crucial for our understanding of the history of the Central Andes. In this paper, we focus on the Atacama … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 66 publications
(95 reference statements)
1
22
0
3
Order By: Relevance
“…1), to the south of our primary study area, suggests that the infi lling of the Central Depression began with the burial of an Oligocene erosional landscape formed during a more pluvial period, and continued during a long period of declining precipitation. Nalpas et al (2008) concluded that deposition ceased with the onset of hyperarid conditions, between 1 The recent change in the Pliocene-Pleistocene boundary (Gibbard et al, 2009) from 1.8 to 2.6 Ma may ultimately change of some the epoch assignments of the geological mapping units in our fi eld area. In our landscape reconstructions, we use the previously assigned relative geological ages, where the Pleistocene was assigned a beginning at 1.8 Ma.…”
Section: Rates Of Watershed Erosionmentioning
confidence: 86%
See 1 more Smart Citation
“…1), to the south of our primary study area, suggests that the infi lling of the Central Depression began with the burial of an Oligocene erosional landscape formed during a more pluvial period, and continued during a long period of declining precipitation. Nalpas et al (2008) concluded that deposition ceased with the onset of hyperarid conditions, between 1 The recent change in the Pliocene-Pleistocene boundary (Gibbard et al, 2009) from 1.8 to 2.6 Ma may ultimately change of some the epoch assignments of the geological mapping units in our fi eld area. In our landscape reconstructions, we use the previously assigned relative geological ages, where the Pleistocene was assigned a beginning at 1.8 Ma.…”
Section: Rates Of Watershed Erosionmentioning
confidence: 86%
“…The relative thickness of the gravels, approximately tens of meters to ~100 m depending on location (Riquelme et al, 2007), combined with ages of intercalated ashes and ignimbrites, indicates that deposition of these gravels occurred over an extended period of several million years (e.g., Clark et al, 1967;Riquelme et al, 2007). Recent work by Riquelme et al (2007) and Nalpas et al (2008) along the Rio Salado (near Chanaral, Fig. 1), to the south of our primary study area, suggests that the infi lling of the Central Depression began with the burial of an Oligocene erosional landscape formed during a more pluvial period, and continued during a long period of declining precipitation.…”
Section: Rates Of Watershed Erosionmentioning
confidence: 99%
“…En la Región de Atacama, las gravas presentan una gradación vertical que va desde facies sedimentarias fluviales en la base, a facies sedimentarias aluviales en el techo. Esta gradación resulta de la progresiva desecación climática del Mioceno Medio, que origina la actual condición hiperárida del Desierto de Atacama, y del progresivo alzamiento y basculamiento de la región de antearco (Riquelme et al, 2003(Riquelme et al, , 2007Nalpas et al, 2008). La colmatación del relieve por las Gravas de Atacama da paso a la formación del extenso Pediplano de Atacama (Hollingworth, 1964;Sillitoe et al, 1968;Mortimer, 1973).…”
Section: Marco Geomorfológicounclassified
“…1c). A lo largo del Desierto de Atacama, los pedimentos han sido clásicamente asociados a condiciones de relativa quiescencia tectónica y ambientes climáticos áridos (e.g., Sillitoe et al, 1968;Paskoff, 1970;Mortimer, 1973;Alpers y Brimhall, 1988;Montgomery et al, 2001;Riquelme et al, 2003Riquelme et al, , 2007Nishiizumi et al, 2005;Schlunegger et al, 2006;Kober et al, 2007;Farías et al, 2008;Nalpas et al, 2008;Placzek et al, 2009). Los pedimentos corresponden a superficies casi planas, escasamente degradadas por la incisión de los sistemas fluviales, y que resultan de un balance entre alteración del sustrato y transporte de sedimentos (para una discusión reciente ver Strudley y Murray, 2007).…”
Section: Introductionunclassified
“…At 10-8 Ma, the formation of[3-m-thick salic gypsisols have been used to suggest a paleoclimate shift to hyperaridity (\20 mm/year precipitation; Rech et al 2006). Similarly, there are a number of reasons to infer a shift to a hyperarid climate: (1) contemporaneous cessation of supergene oxidation in the Atacama Desert (Sillitoe and McKee 1996;Arancibia et al 2006), (2) termination of channel incision by rivers with sources in the Coastal Cordillera , (3) cessation of Atacama Gravel accumulation by braided rivers with sources in the Western Escarpment (Nalpas et al 2008), and (4) termination of supergene enrichment and mineralization in the Late Miocene, or even later (Fig. 8).…”
Section: Western Escarpment and Coastal Cordilleramentioning
confidence: 99%